PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 144 PEKANBARU - Gustina, Helga Tri; Syahrilfuddin, Syahrilfuddin; Noviana, Eddy (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2019)
This study aims to determine the differences and increase in mathematics learning outcomes of third grade students of Pekanbaru Pekanbaru Elementary School between before (pretest) and after (posttest) applying the Indonesian Realistic Mathematics Education Approach (PMRI). The research method used was an experiment with the research design of one group pretest-posttest. This research was conducted in class III of SD Negeri 144 Pekanbaru in the odd semester of the 2018/2019 academic year on material money math subjects. The research subjects were class III students, amounting to 21 people. Data on mathematics learning outcomes were collected using a test technique in the form of a multiple choice objective test. Based on the results of data analysis and discussion, it can be concluded that there are differences and improvements in mathematics learning outcomes of Grade III students of Pekanbaru Pekanbaru Elementary School between before (pretest) and after (posttest) applying the PMRI approach. This is proven based on the results of data analysis obtained in the study. This difference is based on the results of the t test. Obtained tcount fulfills the criteria of t count> t table or 4.5881> 2.0423. with the average N-Gain of 0.38 included in the medium category with. This shows that Ho is rejected and Ha is accepted, meaning there are differences and improvements in student learning outcomes. Based on the evidence it can be concluded that implementing Indonesian Realistic Mathematics Education (PMRI) has a positive influence on the results of mathematics learning for third grade students of Pekanbaru Elementary School 144